Liver-specific metabolomics characterizes the hepatoprotective effect of saponin-enriched Celosiae Semen extract on mice with nonalcoholic fatty liver disease. (March 2018) - Liu, Feng-Jie; Liang, Dan; Miao, Lan-Yun; Li, Ping; Li, Hui-Jun
Highlights: The hepatoprotection of SECSE on HFD-induced NAFLD was studied. Liver-specific metabolomics characterized the comprehensive metabolic profile. The main metabolic pathways responding to SECSE in NAFLD mice were identified. Abstract: Celosiae Semen, derived from the seeds of Celosia argentea L., has a long history of therapeutic uses for liver diseases in China and Japan. Phytochemical researches revealed a series of saponins from Celosiae Semen, which showed a variety of important pharmacological properties such as anti-hyperlipidemia and hepatoprotection. However, the exact protection mechanism is still looking forward to further elucidation. In present study, a liver-specific metabolomics approach based on gas chromatography-mass spectrometry (GC–MS) was applied to investigate the hepatoprotective effect of saponin-enriched Celosiae Semen extract (SECSE) under high-fat diet (HFD) induced nonalcoholic fatty liver disease (NAFLD). Orthogonal partial least squares discriminant analysis (OPLS-DA) was used to identify different metabolic profiles of liver from C57BL/6 mice. At the meantime, serum biochemical analysis and liver histopathological examination were performed. The results suggested that SECSE has effective protection to NAFLD, which is associated with energy metabolism, amino acid metabolism and lipid metabolism.